Sustainability Initiatives and Firm Performance in Indian Companies: An Empirical Examination - Fernandez, Vania Maria; Kumar, Rajesh; Fernandez, Manuel; Joseph, Robinson (Journal of Ecohumanism, 2024)
This study examines the impact of Sustainability initiatives initiated by Indian companies on financial performance. The study was based on ESG ranking scores in the Thomson Reuters database, and the sample comprised 418 companies from six different sectors, namely Basic Industry, Energy, Healthcare, Industrials, Technology, and Utilities. Six models of regression were used for the study where the valuation variables of enterprise value to market capitalization and PE ratio were regressed upon the variables of ESG consisting of ESG score, social, governance, and environmental pillar scores, and control variables. The category scores of pillars were used as independent variables. ESG initiatives have a significant positive effect on the firm performance. The study finds that smaller firms tend to have higher valuation effects. Environmental innovative initiatives to reduce environmental costs and create market opportunities through new environmental technologies and processes have positive valuation effects in the market. Firms in the technology sector tend to have higher valuation effects.